Penalty in labor law : compartive study of french law and the law of Mali - (:unkn) unknown (My University, 2012)
The punishment in labor lawSUMMARYMy thesis relates to the study of the right Malian compared to the law the labour French. Mali being an old French colony, there are strong resemblances between the two rights to the level of the definition of applicable sanctions. But the application of the sanctions in these two countries is not made same manner. That is explained for corporate names, cultural and economic. To illustrate the points of convergences and divergences between these two rights, it was necessary to us to analyze the civil sanctions, administrative and penal in the two countries on the basis of in entirety of the law the labour French of before the reform of the law of bearing 13 July 1973 on the control of the real and serious cause of the dismissal until our days in particular the law of June 28 2008 studies on the modernization of the labour market with the example of the article L 1237-11 bearing conventional rupture of the contract of employmentOf this comparison, it appeared relevant to me to make suggestions to improve the law the labour Malian to the image of the French right all while adapting it preparatory project single of the O.H.A.D.A on the law the labour African because of the development of the economic and social market of the world and the place that y occupies in West Africa. By what our fair labor standards act goes back to 1992 and which since this date no reforms significant was not operated.
Keywords: African Research